Research on the configuration path of enterprise data asset value realization: an empirical analysis based on NCA and fsQCA - Huang, Xing; Yang, Xin (Industrial management + data systems, 2025)
PurposeHow to accurately identify the realization path of realizing the value of enterprise data asset is the key to improving enterprise data management ability and building an efficient data governance mechanism.Design/methodology/approachFrom the perspective of information ecosystem theory, an empirical study was conducted using necessity condition analysis (NCA) and fuzzy set qualitative comparison method (fsQCA) based on 285 questionnaire data. Analyze the impact of multi factor linkage in the dimensions of subject, object, and environment on the realization of enterprise data asset value.FindingsThe results show that a single factor is not the necessary condition for the formation of enterprise data asset value. There are three configuration paths of Enterprise Data Asset Value Formation: subject-object-environment joint driving type, subject-environmental dual drive type and environmentally dominant supported by big data capabilities. In addition, absorption capacity, technology maturity and data resource base are particularly prominent in the process of enterprise data asset value formation.Originality/valueThe research clarifies the path for realizing the value of enterprise data assets and provides insights for data asset management for enterprises.